From the most to the least flexible nutritional profile: Classification of foods marketed in Brazil according to the Brazilian and Mexican models - Tomaz, Luiza Andrade; Pereira, Crislei Gonçalves; Braga, Luiza Vargas Mascarenhas; Prates, Sarah Morais Senna; Silva, Alessandro Rangel Carolino Sales; Soares, Ana Paula da Costa; Faria, Natália Cristina de; Anastácio, Lucilene Rezende (Frontiers in Nutrition, 2022)
To be effective, policies such as front-of-pack nutrition labeling (FoPNL) must have an adequate nutritional profile model. This study aimed to classify products sold in a Brazilian market considering the nutritional profile model of Brazilian (BL) and Mexican FoPNL legislation (ML). This is an observational, cross-sectional study in which we collected information on food products from one supermarket chain in the city of Belo Horizonte-MG/Brazil, in 2021. The products were classified in relation to BL (added sugars, saturated fats, and sodium) and ML (energy, free sugars, saturated fats, trans fats, sodium, sweeteners and caffeine). A total of 3383 products were collected and 3335 products were evaluated. Of these, 2901 would be eligible to receive FoPNL according to BL, and 2914 would be eligible to receive FoPNL according to ML. According to BL, 1639(56.5%) would receive FoPNL, and 1262(43.5%) products would not. For added sugars: 769(26.5%), for saturated fats: 776(26.7%) and 621(21.4%): for sodium would receive FoPNL according to BL. Considering ML, 2821(96.8%) would receive up to 5 FoPNL and up to 2 advised phrases, and only 93(3.2%) products would not, 2124(72.9%) products would receive alerts for energy, 1355(46.5%) for free sugars, 1272(43.7%) for saturated fats, 145(5.0%) for trans fats, 1396(47.9%) for sodium, 461(15.8%) for sweeteners and 18(0.6%) for caffeine. The eligibility to receive FoPNL by BL and ML was relatively similar, however, almost all products would have at least one FoPNL according to ML, and more than half of them, at least one FoPNL, considering BL.